The role of reference groups and destination image on visiting intentions for tourists in East Java - Kristiningsih Kristiningsih; Santirianingrum Soebandhi; Ruswiati Suryasaputra (Jurnal Manajemen dan Pemasaran Jasa, 2022)
This study aims to analyze the interest of tourists to travel during the covid-19 pandemic. The existence of this epidemic certainly changes the behavior of tourists, many things are their consideration before deciding to travel. This study focused on domestic tourists in East Java with the aim of analyzing the attitudes and intentions of tourists to travel (travel intentions) which were influenced by referent groups. This research involved 134 respondents from some traveling location in Malang, Batu and Pasuruan. This research used  accidental sampling and the hypothesis was tested by using the Structural Equation Model analysis technique. The results showed that all hypotheses were met.